A systematic review of fidelity measurements in complex interventions for people with intellectual disabilities and behaviours that challenge. Issue 3 (12th June 2019) - Paulauskaite, Laura; Hassiotis, Angela; Ali, Afia
Abstract : Purpose: Fidelity data in clinical trials are not only necessary for appraising the internal and external validity, but also could provide useful insights how to improve the application of an intervention in everyday settings. The purpose of this paper is to understand the current literature of fidelity measurements in complex interventions for people with intellectual disabilities (ID) and behaviours that challenge. Design/methodology/approach: The electronic databases MEDLINE, Embase, PsycINFO, Web of Science and CINAHL Plus were searched for studies published between 1990 to 2017 that have mentioned fidelity in randomised controlled trials of complex interventions for people with ID and behaviours that challenge based on positive behaviour support or applied behaviour analysis principles. The authors also searched the grey literature and reference lists. Findings: Five randomised controlled trials were included in the review. The authors found variable and inconsistent fidelity measurements reported in the studies. The most frequently provided fidelity elements found in four out of five studies were adherence of implementation, dose and some aspects of quality of delivery. Research limitations/implications: Research recommendations for a standardised approach of measuring fidelity in such studies are suggested. Originality/value: The first review of such type that confirms the paucity of research measuring fidelity in complex interventions in this population.